Smart-trace system - Lim, Emily Ming Jin (2017)
In this FYP, an Android Application named as Smart-Trace System is developed. The Smart-Trace System is a highly user friendly application that simplifies and automates field process, hence creating a convenient, efficient and friendly environment. The Smart-Trace System consist of two separate mobile applications: The Client (Site Engineer) and the Master (Site Supervisor) App. This report will elaborate on the development process of the Smart-Trace System from research and planning, to coding and testing. The design changes could also be observed in the project development chapter. Over a period of eight months, the Smart-Trace System has gone through multiple testing and improvement to achieve all of the targeted milestones as planned.